PEMETAAN KARAKTERISTIK ARUS LALU LINTAS DENGAN METODE GREENBERG PADA RUAS JALAN KOTA MALANG - Fauzi Aldiansyah Aldiansyah; Hendrata Wibisana (Racic : Rab Construction Research, 2024)
The volume of traffic on Jaksa Agung Suprapto Road is quite high and is expected to continue increasing with the growing population. Therefore, an analysis of traffic flow characteristics is necessary. In this study, a mathematical model approach using the Greenberg method was employed. The research and analysis on Jaksa Agung Suprapto Road yielded results using the Greenberg method, with the highest R2 value occurring on Fridays, specifically in segment 7, at 0.89. The variable values obtained for this segment include the Maximum Volume (Vm) at 5523.05 pcu/hour, Free Flow Speed (Uf) at 73.01 km/h, Maximum Speed (Um) at 9.98 km/h, and Saturation Density (Dj) at 1504.53 pcu/km. The application of Geographic Information System (GIS) in this research involved using the research results as attribute data in thematic maps depicting traffic characteristics.